Forkhead Box F1 promotes breast cancer cell migration by upregulating lysyl oxidase and suppressing Smad2/3 signaling - Nilsson, Gisela (BMC Cancer, 2016)
BACKGROUND: Epithelial-mesenchymal transition (EMT) increases cell migration and is implicated in cancer cell invasion and metastasis. We have previously described the involvement of the transcription factors, nuclear factor I-C2 (NFI-C2) and Forkhead box F1 (FoxF1), in the regulation of EMT and invasion during breast tumor progression. NFI-C2 counteracts these processes and FoxF1 is a directly repressed target of NFI-C2. FoxF1 induces EMT and invasiveness and enhances xenograft tumorigenicity in nude mice. Here we identify oppositely regulated targets of NFI-C2 and FoxF1 involved in these processes and further study a possible role for FoxF1 in tumorigenesis. METHODS: We used Affymetrix microarray to detect changes in the transcriptome of a mouse mammary epithelial cell line upon overexpression of NFI-C2 or FoxF1. To elucidate the effects and signaling events following FoxF1 overexpression we investigated in vitro invasion capacity and changes in transcription and protein expression resulting from RNAi and inhibitor treatment. RESULTS: The extracellular matrix enzyme lysyl oxidase (LOX) was negatively regulated by NFI-C2 and positively regulated by FoxF1, and upregulation of LOX following FoxF1 overexpression in mouse mammary epithelial cells increased in vitro cell invasion. In the nuclei of FoxF1-overexpressing cells, the phosphorylation of Smad2 decreased, while that of p38 increased. Depletion of LOX by RNAi enhanced phosphorylation of Smad2 by a focal adhesion kinase (FAK)-dependent mechanism. In addition, induced expression of FoxF1 in a non-malignant human mammary epithelial cell line showed that the increase in LOX transcription and the suppression of Smad2 activity are early effects of FoxF1. CONCLUSION: These data show that FoxF1 enhances invasion in a LOX-dependent manner, is involved in the regulation of Smad2 signaling, and that FoxF1 overexpression ultimately leads to activation of p38 MAPK signaling. These findings provide new insights into the regulation of signaling pathways known to be important during breast tumor progression. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12885-016-2196-2) contains supplementary material, which is available to authorized users.